Adsorption characteristics and mechanisms of high-levels of ammonium from swine wastewater using natural and MgO modified zeolites. Issue 12 (8th March 2016) - Guo, Junyuan
Abstract: This paper focuses on the effectiveness of removing ammonium by both natural and MgO modified zeolites and the theoretical aspects of adsorption including mechanisms. Results have demonstrated that the zeolite synthesized by integrated calcination with MgO at 400°C performances a good ammonium adsorption capacity as high as 24.9 mg g −1, an increase by 97.6 and 68.2% compared to that of natural zeolite itself and natural zeolite that heated in 400°C for 4 h (12.6 and 14.8 mg g −1, respectively), when its dose was adjusted at 27 g L −1 with solution pH of 8.3 and agitation speed of 280 r min −1 at 25°C. Negative Gibbs free energy change indicated the spontaneous nature of the adsorption. In addition, both ion-exchange and molecular adsorption being the main mechanisms, in which ion-exchange dominated the ammonium adsorption process near neutral pH, and the molecular adsorption was of secondary importance, and contributed less to the total ammonium removal according to the experimental results under neutral pH conditions.